PENGGUNAAN KLAUSA RELATIF DALAM ANIMASI UPIN IPIN EPISODE SIAMANG TUNGGAL: KAJIAN TIPOLOGI LINGUISTIK - Zahra Rifasyah; Mulyadi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to examine the forms and functions of relative clauses in the animated film Upin Ipin: Siamang Tunggal through a linguistic typology approach. It focuses on how relative clauses are constructed and utilized in character dialogues, representing contemporary Malaysian Malay. The study employs a descriptive qualitative method and analyzes data based on typological theories by Comrie and Keenan. The findings reveal that all relative clauses in the film employ the marker yang, most of which are restrictive clauses where the relativized element functions as the subject. The relative clause structures follow a consistent head-initial pattern and the basic SVO sentence order, which are typological features of Malay. Beyond syntactic function, relative clauses also contribute significantly to the narrative and rhetorical structure of the film. These findings affirm that linguistic data drawn from popular media such as animation can serve as valid and meaningful sources for linguistic inquiry.